2013
DOI: 10.1186/1752-153x-7-99
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of mycotoxins in wheat from western Romania and histopathological impact as effect of feed intake

Abstract: BackgroundThe goal of this study has been to evaluate the extent of mycotoxins contamination and their co-occurrence in wheat grain intended for animal feed. A total of 52 wheat samples were collected from the harvest of two consecutive years (2010, 2011) from two counties (Timis and Arad) located in Western Romania and the presence of ochratoxin A (OTA), deoxynivalenol (DON), zearalenone (ZON) and fumonisins (FUMO) was determined by enzyme-linked immunosorbent assay (ELISA). In order to evaluate the toxicolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…In-field cereal contamination with DON is frequent in the Western and Northern regions where F. graminearum and F. culmorum are predominant, while it is sporadic and low in the Southern and Eastern areas [10,11,12,13,14,15,17,26,31]. Although there were reports of high DON contamination in grains during harvest in 2012, 2013, and 2014 [17,26], the present post-harvest study found low contamination, except in wheat flour type 450 obtained from wheat in 2014.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In-field cereal contamination with DON is frequent in the Western and Northern regions where F. graminearum and F. culmorum are predominant, while it is sporadic and low in the Southern and Eastern areas [10,11,12,13,14,15,17,26,31]. Although there were reports of high DON contamination in grains during harvest in 2012, 2013, and 2014 [17,26], the present post-harvest study found low contamination, except in wheat flour type 450 obtained from wheat in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Post-harvest contamination with OTA showed an inversely significant correlation with the mean annual temperature, a significant correlation with the cumulative precipitation in all years, and, finally, a dependence on chernozem soils with high aridity indices. In Romania, cereal contamination with OTA has been reported in both the Southeastern region, which features a semi-arid temperate continental climate, as well as in the Western region, with has a semi-wet temperate continental climate [11,12,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on fumonisin occurrence in wheat from Europe have not been identified, with the only exception of a study from Western Romania (Alexa et al., ). The authors reported for FB 1 a 15% of frequency in wheat, with a contamination range of 960–1,180 μg/kg.…”
Section: Assessmentmentioning
confidence: 99%
“…Mycotoxin occurrence in animal feed has been reported from various countries: AFB 1 in Kenya (Kang’ethe and Lang'a ), cyclopiazonic acid in India (Balachandran and Parthasarathy ), ZEA and DON in Romania (Alexa and others ), citrinin in Russia (Kononenko and Burkin ), and OTA in Argentina (Dalcero and others ).…”
Section: Mycotoxin Contamination Of Food and Feed In Pakistanmentioning
confidence: 99%